Adsorption of chrysene in aqueous solution onto MIL-88(Fe) and NH2-MIL-88(Fe) metal-organic frameworks: Kinetics, isotherms, thermodynamics and docking simulation studies. Issue 2 (April 2020) - Zango, Zakariyya Uba; Abu Bakar, Noor Hana Hanif; Sambudi, Nonni Soraya; Jumbri, Khairulazhar; Abdullah, Nor Ain Fathiha; Kadir, Evizal Abdul; Saad, Bahruddin
Highlights: High porous and crystalline MIL-88(Fe) and NH2 -MIL-88(Fe) MOFs. Effective adsorption of Chrysene in aqueous solution onto the MOFs Shorter equilibration time of 25 min. Easy regeneration and re-usability of the MOFs for the chrysene adsorption. Molecular docking simulations for binding interactions between the MOFs with the CRY. Abstract: MIL-88(Fe) and NH2 -MIL-88(Fe) metal-organic frameworks were synthesized using the microwave-assisted solvothermal method and were characterized using scanning electron microscopy (SEM), Brunauer Emmett Teller (BET), powdered X-ray diffraction (XRD) and Fourier transformed infrared (FTIR) spectroscopy. Relatively high surface areas with corresponding pore volumes of 1240 m 2  g −1 and 0.7 m 3  g −1, 941 m 2  g −1 and 0.6 m 3  g −1 were found for MIL-88(Fe) and NH2 -MIL-88(Fe), respectively. The MOFs were evaluated as adsorbent for the removal of chrysene (CRY) in water. Important parameters that affect the adsorption such as contact time, initial concentration of CRY, pH and temperature were systematically studied. Adsorption isotherms using Langmuir, Freundlich and Temkin models were investigated. Other details of the adsorption process were also studied using kinetics and thermodynamics approaches. Additionally, molecular docking was used to unravel the nature of the adsorption between the MOFs and CRY. The reusability of the adsorbents was evaluated using regeneration studies. In conclusion, these MOFs exhibit favorable characteristics to be used for the removal of CRY from water.